Policijsko delo v skupnosti in partnersko zagotavljanje varnosti v lokalnih skupnostih - Meško, Gorazd; Eman, Katja; Modic, Maja; Hacin, Rok (University of Maribor Press, 2024)
Community Policing and Partnership in Ensuring Safety and Security in Local Communities. The monograph presents community policing in the context of ensuring safety and security in local communities in Slovenia. In the introduction, the theoretical perspectives of police work in the community are presented, followed by a systematic review of European research on community policing in the last two decades. The authors discuss the connection between legitimacy and community policing from the perspective of public opinion on the police and police officers’ self-legitimacy and their views on the police organization. The authors also focus on community policing in urban and rural environments, as the nature of crime and policing differs between the settings. The presentation of focus group interviews with police officers and individual semi-structured interviews with representatives of local communities follows. In the following chapter, the authors present a SWOT analysis of community policing. The authors conclude with a reflection on the development of policing in Slovenia in the last three decades.